2013
DOI: 10.1016/j.jare.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical synthesis of 1,2,4,5-tetrasubstituted imidazoles using nanocrystalline MgAl2O4 as an effective catalyst

Abstract: An efficient four-component synthesis of 1,2,4,5-tetrasubstituted imidazoles is described by one-step condensation of an aldehyde, benzil, ammonium acetate and primary aromatic amine with nanocrystalline magnesium aluminate in ethanol under ultrasonic irradiation. High yields, short reaction times, mild conditions, simplicity of operation and easy work-up are some advantages of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 34 publications
0
24
0
4
Order By: Relevance
“…Afterward several methods have been reported for the synthesis of tri-substituted imidazoles by cyclo condensation of 1,2 dicarbonyl compounds, various aromatic aldehydes and ammonium acetate using various catalysts such as NiCl 2 •6H 2 O/Al 2 O 3 [15], MoO 3 /SiO 2 [16], Polymer supported zinc chloride [17], trichloro isocyanuric acid (TCCA) [18] under reflux conditions and glyoxalic acid as catalyst under microwave conditions [19] and Zinc (II) (tetra (4-methylphenyl)) porphyrin [20], Magnetic Fe 3 O 4 nano particles [21], Sulfamic acid functionalized magnetic nano particles SA-MNP [22], Ionic liquid (EMIM)OAc [23], Zr(acac) 4 [24], ceric ammonium nitrate [25] as catalysts under ultra sound assisted conditions. In the same way several methods have been reported for the synthesis of tetra substituted imidazoles by cyclo condensation of 1,2 dicarbonyl compounds, various aromatic aldehydes, ammonium acetate and aromatic/aliphatic amines using various catalysts such as nano TiCl 4 •SiO 2 [26] [33] as catalyst under Ultra sound irradiation. In extension with these procedures, several methods have been reported for the synthesis of both tri and tetra substituted imidazoels using various catalysts such as molecular Iodine [34], Sodium dihydrogen phosphate [35], BiCl 3 [36], DABCO [37] According to the literature survey, several synthetic protocols have been reported for the synthesis of substituted imidazoles using various type of copper containing catalyst such as synthesis of imidazoles through the Cu 2 O catalyzed cross-cycloaddition between two different isocyanides [43], Synthesis of 1,2,4-trisubstituted imidazoles through the CuCl 2 -catalyzed oxidative diamination of terminal alkynes by amidines [44], Synthesis of multi substituted imidazoles via CuI-catalyzed [3 + 2] cycloadditions [45].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Afterward several methods have been reported for the synthesis of tri-substituted imidazoles by cyclo condensation of 1,2 dicarbonyl compounds, various aromatic aldehydes and ammonium acetate using various catalysts such as NiCl 2 •6H 2 O/Al 2 O 3 [15], MoO 3 /SiO 2 [16], Polymer supported zinc chloride [17], trichloro isocyanuric acid (TCCA) [18] under reflux conditions and glyoxalic acid as catalyst under microwave conditions [19] and Zinc (II) (tetra (4-methylphenyl)) porphyrin [20], Magnetic Fe 3 O 4 nano particles [21], Sulfamic acid functionalized magnetic nano particles SA-MNP [22], Ionic liquid (EMIM)OAc [23], Zr(acac) 4 [24], ceric ammonium nitrate [25] as catalysts under ultra sound assisted conditions. In the same way several methods have been reported for the synthesis of tetra substituted imidazoles by cyclo condensation of 1,2 dicarbonyl compounds, various aromatic aldehydes, ammonium acetate and aromatic/aliphatic amines using various catalysts such as nano TiCl 4 •SiO 2 [26] [33] as catalyst under Ultra sound irradiation. In extension with these procedures, several methods have been reported for the synthesis of both tri and tetra substituted imidazoels using various catalysts such as molecular Iodine [34], Sodium dihydrogen phosphate [35], BiCl 3 [36], DABCO [37] According to the literature survey, several synthetic protocols have been reported for the synthesis of substituted imidazoles using various type of copper containing catalyst such as synthesis of imidazoles through the Cu 2 O catalyzed cross-cycloaddition between two different isocyanides [43], Synthesis of 1,2,4-trisubstituted imidazoles through the CuCl 2 -catalyzed oxidative diamination of terminal alkynes by amidines [44], Synthesis of multi substituted imidazoles via CuI-catalyzed [3 + 2] cycloadditions [45].…”
Section: Introductionmentioning
confidence: 88%
“…The plausible mechanism for the synthesis of 1,2,4,5-tetra substituted imidazoles [33] with the copper nano ferrite in the reaction may be shown in Scheme 4. Ammonium acetate is the source of ammonia molecule.…”
Section: Plausible Mechanism For the Formation Of Products Under Nanomentioning
confidence: 99%
“…In a more-oriented synthetic application, Safari et al reported a convenient synthesis of 1,2,4,5-tetrasubstituted imidazoles (70) through a four-component one-step condensation of a substituted aromatic aldehyde (67), benzyl (68), phenyl amine (69), and ammonium acetate with nanocrystalline magnesium aluminate (MgAl2O4) in ethanol under ultrasound (Scheme 22) [115]. The protocol show the typical advantages of sonochemically accelerated reactions in terms of high yields, mild conditions, short reaction times, and easy work-up.…”
Section: Main-group Npsmentioning
confidence: 99%
“…Synthesis of imidazole ring and its derivatives is carried out by using one-step condensation of diketone with aldehyde, ammonium acetate and primary aromatic amine in the presence of nanocrystalline magnesium aluminate (Safari et al, 2013), supported ionic liquidlike phase (Saffari Jourshari et al, 2013), SiO2-Pr-SO3H , clay supported titanium catalyst (Kannan and Sreekumar, 2013), brønsted acidic ionic liquid,(4-sulfobutyl)tris(4-sulfophenyl)phosphonium hydrogen sulfate (Banothu et al, 2013), nano-TiCl4.SiO2 (Mirjalili et al, 2012) I2/Cs2CO3 (Xue et al, 2014) and sulfonic acid functionalized SBA-15 nanoporous material (SBA-Pr-SO3H) catalyst .…”
Section: Introductionmentioning
confidence: 99%